2007
DOI: 10.1088/0957-4484/18/38/385602
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a precursor layer in self-assembled CdTe quantum dots grown on ZnSe by molecular beam epitaxy

Abstract: The growth mode of CdTe quantum dots (QDs) grown on highly lattice-mismatched ZnSe buffer was investigated. CdTe QDs (0.6 to 5.0 mono-layers (MLs)) were deposited on the Se-stabilized ZnSe buffer layers using an alternating supply of Cd and Te atomic sources. Cross-sectional transmission electron microscopy and photoluminescence (PL) measurements revealed the existence of a CdSe-like two-dimensional precursor layer (PCL). The prominent difference in the temperature-dependent PL peak shift was associated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…This has precluded spectroscopy of individual QDs in such mixed type systems so far. 2,3,[29][30][31][32][33][34] Cd(Se,Te)/ZnSe QDs presented in this letter are grown by molecular beam epitaxy on a 1 µm thick ZnSe buffer deposited on a GaAs substrate. They form in a self-assembled mode out of atomic layers of Se, Cd, Te, Cd, and Se (each one for time of 15 sec) consecutively deposited at temperature of the substrate set to 335 • C. An approximately monolayer thick CdSe layer (a CdSe = 0.608 nm) inserted between CdTe layer and ZnSe diminishes the strain resulting from the CdTe and the ZnSe lattice mismatch.…”
Section: Cd(sete)/znse Quantum Dots Produced By a Mn-assisted Epitaxi...mentioning
confidence: 99%
“…This has precluded spectroscopy of individual QDs in such mixed type systems so far. 2,3,[29][30][31][32][33][34] Cd(Se,Te)/ZnSe QDs presented in this letter are grown by molecular beam epitaxy on a 1 µm thick ZnSe buffer deposited on a GaAs substrate. They form in a self-assembled mode out of atomic layers of Se, Cd, Te, Cd, and Se (each one for time of 15 sec) consecutively deposited at temperature of the substrate set to 335 • C. An approximately monolayer thick CdSe layer (a CdSe = 0.608 nm) inserted between CdTe layer and ZnSe diminishes the strain resulting from the CdTe and the ZnSe lattice mismatch.…”
Section: Cd(sete)/znse Quantum Dots Produced By a Mn-assisted Epitaxi...mentioning
confidence: 99%
“…Advances in the growth technology of II-VI semiconductors now permit the growing of high-quality ZnCdTe/ZnTe QDs. 6,7) On the theoretical side, it has recently been reported that the strain significantly affects the energy band structures of the strained CdTe/ZnTe QD system. 8) However, many fundamental electronic and optical properties of this system are not yet well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in a growth technology of II-VI semiconductors now permit the growing of high-quality CdTe/ZnTe QDs. [3,4] Recently, several groups have studied the wetting layer effect on electronic and optical properties of QDs. For example, Lee et al [5] showed that for a selfassembled InAs/GaAs lens-shaped QD, the inclusion of a wetting layer weakens the strain inside the dot by 1%, while it reduces the transition energy between a confined electron and hole level by as much as 10%.…”
mentioning
confidence: 99%